2016
DOI: 10.12659/msm.899179
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Silencing of S100A8 Gene by miR-24 to Increase Chemotherapy Sensitivity of Endometrial Carcinoma Cells to Paclitaxel

Abstract: BackgroundThe objective of this study was to determine whether miR-24 can regulate malignant proliferation and chemotherapy sensitivity of EC cells by targeted silencing of the S100 Calcium Binding Protein A8 (S100A8) gene.Material/MethodsThe expression of miR-24 in EC tissues was detected by quantitative real-time PCR. The proliferation ability and chemotherapy sensitivity were analyzed by MTT assay. Bioinformatics software was used to predict some potential target genes of miR-24. Luciferase activity assay w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…Similar effects were observed for miR-24, a miRNA targeting S100A8, which inhibited proliferation and invasion of laryngeal carcinoma cells [242]. Besides, it was shown that S100A8-silencing by miR-24 reduced proliferation but enhanced sensitivity to paclitaxel of endometrial carcinoma cells [243]. Another interesting approach demonstrated that miR-6884-5p targets the expression of S100A16, which resulted in reduced proliferation, EMT, and invasion of gastric cancer cells in vitro [244].…”
Section: Micro Rna (Mirna) Mimicssupporting
confidence: 52%
See 1 more Smart Citation
“…Similar effects were observed for miR-24, a miRNA targeting S100A8, which inhibited proliferation and invasion of laryngeal carcinoma cells [242]. Besides, it was shown that S100A8-silencing by miR-24 reduced proliferation but enhanced sensitivity to paclitaxel of endometrial carcinoma cells [243]. Another interesting approach demonstrated that miR-6884-5p targets the expression of S100A16, which resulted in reduced proliferation, EMT, and invasion of gastric cancer cells in vitro [244].…”
Section: Micro Rna (Mirna) Mimicssupporting
confidence: 52%
“…S100A8 silencing leads to decreased proliferation and invasion of laryngeal carcinoma cells and increases sensitivity of endometrial carcinoma cells for paclitaxel Pre-clinical [242,243] miR-6884-5p S100A16 S100A16 silencing reduces proliferation, invasion, and EMT in gastric cancer Pre-clinical [244] 3.…”
Section: S100a4 Silencing Results In Inhibition Of Invasion and Migramentioning
confidence: 99%
“…reported to be associated with a variety of diseases by acting on different signaling pathways (24). The present study aimed to determine the association between miR-24 expression levels in vasospasm following SAH and its underlying mechanism.…”
Section: Nos3 Is a Predicted Target Gene Of Mir-24 Mir-24 Has Beenmentioning
confidence: 93%
“…18,19 After 48 h, the cellular viability was detected, and the inhibition rate for every concentration and the half maximal inhibitory concentration (IC 50 ) were calculated using GraphPad5 software (Graphpad Software, La Jolla, CA).…”
Section: Chemoresistance Assaymentioning
confidence: 99%